Recent advances in the management of proliferative diabetic retinopathy. Issue 3 (3rd May 2023) - Pandit, Saagar; Ho, Allen C.; Yonekawa, Yoshihiro
Abstract : Purpose of review: The prevalence of diabetic retinopathy continues to rise. This review highlights advances in imaging, medical, and surgical management of proliferative diabetic retinopathy (PDR) in recent years. Recent findings: Ultra-widefield fluorescein angiography has been shown to better characterize which patients have predominantly peripheral lesions and who may advance to more advanced forms of diabetic retinopathy. This was well demonstrated in DRCR Retina Network's Protocol AA. Protocol S demonstrated that antivascular endothelial growth factor (VEGF) treatment alone can be useful in the management of select PDR patients – particularly those without high-risk features. However, a growing body of literature highlights how lapse in care is a significant concern in PDR patients, and tailoring one's approach to treatment based on patient needs is recommended. In patients with high-risk features or where there is concern for lost-to-follow-up, incorporation of panretinal photocoagulation in the treatment paradigm is recommended. Protocol AB highlighted how patients with more advanced disease may benefit from earlier surgical intervention for earlier visual recovery but that continued anti-VEGF treatment may result in similar visual outcomes over a longer period. Finally, earlier surgical intervention for PDR without vitreous hemorrhage (VH) or retinal detachment is being considered a potential option to minimize treatment burden. Summary: Recent advances in imaging, as well as medical and surgical treatment options for PDR, have provided a deeper understanding of PDR management, which can be optimized for the individual patient.